Garbage In, Gospel Out? : Controlling for the Underreporting of Remittances - Melkonyan, Tigran; Grigorian, David; Shonkwiler, J. Scott (Washington, D.C. : International Monetary Fund, 2008)
Empirical studies that use self-reported data on remittances to measure the latter's impact on microeconomic incentives mostly ignore the potential errors associated with reporting/measurement issues. An econometric procedure to control for these errors is developed and applied to household-level data from Armenia. We find evidence of systematic under-reporting of remittances. After controlling for this, we find a strong negative impact of remittances on incentives to work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet